Manajemen Bimbingan Belajar di Sekolah SMA Negeri 1 Langkaplancar Pangandaran - Sri Nurhilmi Fauziah; Nada Nurfadilah; Asep Saepudin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
The tutoring is a process of providing assistance to individuals that is carried out continuously so that a change occurs within the individual. The aim of the research is to explore how tutoring is managed at SMA Negeri 1 Langkaplancar Pangandaran. This research method is a qualitative descriptive research method. The technique in this research uses observation, interviews and documentation methods. The results of the research show that the management of tutoring at SMA Negeri 1 Langkaplancar is prepared through certain programs, namely guidance and counseling programs which have been included in scheduled activity plans, so that they can help students achieve optimal development.